2019
DOI: 10.1111/irv.12677
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neopterin and indoleamine 2,3‐dioxygenase activity in patients with seasonal influenza: A pilot study

Abstract: BackgroundSeasonal influenza is an important cause of morbidity and mortality worldwide. Immune activation after stimulation with interferon‐gamma leads to increased production of neopterin but also results in increased tryptophan catabolism through indoleamine 2,3‐dioxygenase (IDO). Our pilot study determined neopterin serum levels and IDO activity in patients with influenza infection and investigated whether neopterin is linked to clinical outcome parameters (mortality ≤30 days, acute cardiac events (ACE) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…There are several studies focused on the prognostic value of neopterin in various viral infections. Pizzini et al 12 showed that a higher level of neopterin was associated with the lengthened hospitalization and increased risk of acute cardiac events in seasonal influenza patients. In HIV infected population, serum neopterin levels were correlated with increased viral load and mortality 14,19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies focused on the prognostic value of neopterin in various viral infections. Pizzini et al 12 showed that a higher level of neopterin was associated with the lengthened hospitalization and increased risk of acute cardiac events in seasonal influenza patients. In HIV infected population, serum neopterin levels were correlated with increased viral load and mortality 14,19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…The level of serum neopterin reflects the stage of activation of the cellular immune system, which is important in the pathogenesis and progression of various diseases 11 . In previous studies, the relationship between neopterin serum levels and prognosis has been shown in some viral infections such as influenza, human immunodeficiency viruses, hepatitis C virus, dengue fever virus 12–14 . In severe acute respiratory syndrome (SARS) patients, serum neopterin has been reported to be a useful marker in the early assessment of disease severity 15 …”
Section: Introductionmentioning
confidence: 99%
“…The Kyn:Trp ratio, measured in blood, is a valuable clinical benchmark of IDO-1 activation, and reflects the state of immune activation or tolerance in cancer immunity, autoimmunity, infection and other disorders. Changes in Kyn:Trp ratio have been associated with viral infections, such as HIV and HIV-human herpes virus co-infection [ 14 ], seasonal influenza [ 15 ], Dengue virus [ 16 ], and HBV [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, various types of viral infections are able to activate the formation and release of INF-γ from infected cells, where INF-γ stimulates macrophages to produce and release of NPT. Therefore, NPT concentrations reflect an underlying cell-mediated immune activation [ 18 ].…”
Section: Characteristics and Role Of Neopterinmentioning
confidence: 99%